Leo letreros y senales - Hoban, Tana. (New York : Scholastic, 1995)
Introduces signs and symbols frequently seen along the street.
Between the Lions recommended books.
Keywords: Traffic signs and signals -- Juvenile literature; Street signs -- Juvenile literature; Signs and signboards -- Juvenile literature; Spanish language materials -- Juvenile literature; Picture books